2016
DOI: 10.5253/arde.v104i3.a7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Size of the Dutch Breeding Population of Continental Black-Tailed Godwits from 2007–2015 Using Resighting Data from Spring Staging Sites

Abstract: Over the past 50 years, the population of Continental Black-tailed Godwits Limosa limosa limosa breeding of the East Atlantic Flyway has been in steep decline. This decline has previously been documented in trend analyses and six Netherlands-wide count-based population estimates, the last of which was completed in 1999. We provide an updated population size estimate and describe inter-annual fluctuations in the population between 2007 and 2015. To generate these estimates, we integrated a mark-recapture surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 40 publications
3
40
2
4
Order By: Relevance
“…Black‐tailed Godwit Limosa limosa limosa; Kentie et al . ) and to the point of being threatened with global extinction (e.g. Spoon‐billed Sandpiper Calidris pygmaea ; Zöckler et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Black‐tailed Godwit Limosa limosa limosa; Kentie et al . ) and to the point of being threatened with global extinction (e.g. Spoon‐billed Sandpiper Calidris pygmaea ; Zöckler et al .…”
mentioning
confidence: 99%
“…Many shorebird populations are currently declining (Delany et al 2009, Pearce-Higgins et al 2017, some very rapidly (e.g. Black-tailed Godwit Limosa limosa limosa; Kentie et al 2016) and to the point of being threatened with global extinction (e.g. Spoon-billed Sandpiper Calidris pygmaea; Z€ ockler et al 2010).…”
mentioning
confidence: 99%
“…In a recent study, Kentie et al. () showed that between 2011 and 2015, black‐tailed godwits have experienced an accelerated population decline of 6.3% per annum. With the remaining Dutch population comprising only 33,000 remaining breeding pairs, pro‐active management of breeding habitat quality is necessary if we hope to reverse the current population trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The continental black‐tailed godwit ( Limosa limosa limosa , Linnaeus, 1758) is a species that is now strongly declining due intensification of agricultural practices (Kentie et al., ). Over 80% of the East‐Atlantic Flyway population of this species breed in The Netherlands, individuals are relatively long‐lived, site faithful (Kentie, Both, Hooijmeijer, & Piersma, ) and reasonably tolerant of land‐use intensification (Bakker & Berendse, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation